IDENTIFICATION OF THE MATHEMATICAL MODELS OF THE TECHNOLOGICAL OBJECTS FOR ROBUST CONTROL SYSTEMS - Lutska, N. M.; Ladanyuk, A. P.; Savchenko, T. V. (Radio Electronics, Computer Science, Control, 2019)
Context. The problem of identification of the mathematical models of the technological objects on the basis of which the robust control system is subsequently synthesized has been considered. The methods of identification of the mathematical models of the technological objects for robust control are the target of the research. Objective. The purpose of the research is to develop recommendations for the existing methods of identifying the mathematical models of the technological objects for robust control to allow the effective application of the robust control systems as well as to increase the energy efficiency of the system as a whole. Method. The suggested recommendations for the identification of the mathematical models of the technological objects aimed at the further synthesis of robust control are divided into two types – with a known and an unknown area of uncertainty. For the former with the mathematical model which is identified only in the nominal mode the existing methods for identifying the continuous models in accordance with the experimentally obtained data are preferable. Taking the multidimensionality and multiplicity of most technological objects into account, the structure of the model in the space of time variables is recommended. It has been suggested to reduce the area of uncertainty to the additive or multiplicative form for the identification of the mathematical models for which, in addition to the nominal model, identification of the area of uncertainty is stipulated. In this case, several models in different operating object modes are used, while the uncertainty is calculated as the distance between the nominal and other models on the frequency grid with the further approximation of the filters of the preassigned order. Results. The suggested algorithm for identifying the mathematical models with the area of uncertainty has been implemented and investigated for a production object – the subsystem of the levels of the diagonal extraction plant of a sugar-mill. Conclusions. The performed experiments have confirmed the efficiency of the proposed calculation of the area of uncertainty of the mathematical models of the technological objects, while the proposed recommendations for the identification of the mathematical models for robust control can be used in practice. Further research is aimed at identifying the area of uncertainty of the closed control systems.